Lugares de começos – Guardiões de memórias: onde se começaram a desenhar formas de pensar e fazer educação, mediação e participação - Dias, Andreia (2025)
We believe in the depth of transformation latent in the combination of art and education, or in art as a way of proposing education. This union generates places of relationship where each person can meet themselves, the other and the others in themselves, and new ways of thinking about the key issues of contemporaneity, taking as a starting point the joint and sensitive construction of a fairer and more democratic society. This article reflects the realization of an artistic-cultural project, which we called Guardians of Memories built by many hands and many heads and subjectivities, in an exercise of co-creation between the school, the museum, which took off from art places and whose transdisciplinary approaches promoted moments of self-discovery and appreciation of the interpersonal and intercultural differences of all those involved. We're talking about a pioneering project between the a School Group and the a foundation with two art collections - two museums, and a starting point for thinking about the importance of artistic and cultural mediation projects, born of the school-museum union, and the importance of fruitful partnerships between the two, in the integral formation of people, regardless of their ages and diversities, and as a contribution to full citizenship. This partnership, which has decentralized both the school and the museum and created new territories and possibilities, has given rise to other ways of thinking about mediation and education, new rhizomatic paths that have expanded and been implemented in ways of doing things on both sides.